The effect of environmental management accounting practices and innovation on Malaysian organizations’ (ISO 14001) competitive advantage and performances / Mohd Sobre Ismail - Ismail, Mohd Sobre (2013)
The growing demand for environmental protection had pushed organizations to become more environmentally responsible. In order to react to the demand of environmentally conscious society, organizations must incorporate environmental agenda in their corporate strategy. The adoption of environmental management accounting practices would help organizations to realize significant costs saving, enhance organizational competitiveness and improve organizations’ performances. Besides that, practicing environmental management accounting would also stimulate innovation in an organization. However, some previous studies revealed those organizations which implemented environmental management accounting practices were unable to realize those benefits. Due to the inconsistency of the previous studies’ results, the present study tries to shed light on the relationship between environmental management accounting practices and innovation and, organizations’ competitive advantage and performances. An online survey had been deployed to ISO 14001 certified Malaysian organizations’ chief executive officer, managing directors, financemanager or key personnel involved in environmental management. 36 usable responses were received and analyzed using SPSS version 21. The present study showed that environmental management accounting practices would enhance organizational competitiveness and organization’s competitive advantage would then improve organizational performances. Therefore, these results would promote organizations which had yet to incorporate environmental agenda in their corporate strategy to adopt environmental management accounting practices which suggest that not only the environment can be preserved, the practices also would enhance organizational competitiveness and thus improve organizational performances.